2018
DOI: 10.3390/ijms19020478
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Telomerase Activity in Cancer Cells by Dietary Compounds: A Review

Abstract: Telomerase is expressed in ~90% of human cancer cell lines and tumor specimens, whereas its enzymatic activity is not detectable in most human somatic cells, suggesting that telomerase represents a highly attractive target for selective cancer treatment. Accordingly, various classes of telomerase inhibitors have been screened and developed in recent years. We and other researchers have successfully found that some dietary compounds can modulate telomerase activity in cancer cells. Telomerase inhibitors derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 117 publications
(145 reference statements)
0
30
0
Order By: Relevance
“…Hrq1 also caused a stalling event at T25, but this effect was weaker than that observed with Pif1 ( Fig. 3A lanes [5][6][7][8]. Unlike Pif1, however, Hrq1 caused an increase in the amount of signal (i.e., decreased processivity) at positions T28 and T30 (Fig.…”
Section: Hrq1 Increases Telomerase Activity In a Displacement Assaymentioning
confidence: 78%
See 1 more Smart Citation
“…Hrq1 also caused a stalling event at T25, but this effect was weaker than that observed with Pif1 ( Fig. 3A lanes [5][6][7][8]. Unlike Pif1, however, Hrq1 caused an increase in the amount of signal (i.e., decreased processivity) at positions T28 and T30 (Fig.…”
Section: Hrq1 Increases Telomerase Activity In a Displacement Assaymentioning
confidence: 78%
“…For instance, the transcription of human TERT can be altered genetically and epigenetically in cancers, leading to upregulation of telomerase activity (5). Similarly, the transcription of genes encoding telomerase components and telomerase activity itself can be up-or downregulated by various dietary compounds (6). Post-translational modifications of TERT, such as phosphorylation (7) and ubiquitination (8), also affect telomerase activity.…”
Section: ________________________________________mentioning
confidence: 99%
“…As this vitamin E family cannot be synthesized in the human body, these nutrients must be supplied exogenously through diet. Recent discoveries have indicated that vitamin E exhibits various potentially beneficial effects on human health, such as anti‐allergic , anti‐atherogenic , anti‐cancer , anti‐cardiovascular , anti‐diabetic , anti‐lipidemic , anti‐hypertensive , anti‐inflammatory , anti‐obesity , neuroprotective , and modulation of telomerase activities . In this review, we introduce the relationship between vitamin E and redox interactions with (i) absorption, distribution, metabolism, and excretion (ADME) of vitamin E, (ii) oxidative stress and reactive oxygen species (ROS) in the body, (iii) mechanism of antioxidative effects, (iv) non‐antioxidant functions of vitamin E, and (v) recent recognition of the field of oxidative stress research.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the transcription of human TERT can be altered genetically and epigenetically in cancers, leading to up-regulation of telomerase activity (5). Similarly, the transcription of genes encoding telomerase components and telomerase activity itself can be up-or down-regulated by various dietary compounds (6). Post-translational modifications of TERT, such as phosphorylation (7) and ubiquitination (8), also affect telomerase activity.…”
mentioning
confidence: 99%